Lixamento do Pinus elliotti com carbeto de silício e óxido de aluminio - Leite, Sueli Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
The Sanding is a complex process involving many variables that affect the quality of the part produced, working mainly in the timber industry in the production of panels (MDF, MDP, HDF, etc...) and furniture. However, these industries use the sanding process empirically, not optimizing it. The aim of this study was to compare the behavior of sandpaper white aluminum oxide (OA-white) and Black silicon carbide (SiC-black), analyzing variables in the process as: strength, power, emission, vibration, wear particle size of sanding, and its consequences on the surface finish of the workpiece. Made the process of plane grinding samples of Pinus elliottii, processed in parallel to the fibers, which were sanded with sandpaper grain OA white and black 3-SiC abrasive conditions (new, moderately eroded and severely eroded) grain sizes in 3 (80, 100, and 120 mesh). 6 replicates was performed for each condition tested. Each trial was captured output variables of the sanding process: strength, power, emission and vibration. With two stages totaling 108 trials. After the sanded samples, it has the same surface quality by raising the surface roughness Ra. Through experiment, it can be concluded that abrasives OA-white tended to have higher strength, power, emissions and less vibration in the sanding process, compared to the SiC-black. However, surface finish exhibited similar to the particle size of 80 to 100 mesh, worn abrasive conditions. However, the particle size of 120 mesh, obtained by the roughness of sandpaper OA-bank was higher compared to SiC-black to all conditions of sandpaper due to its toughness

O lixamento é um processo complexo que envolve inúmeras variáveis que afetam a qualidade da peça produzida, atuando principalmente nas indústrias madeireiras na produção de painéis (MDF, MDP, HDF, etc.) e móveis. No entanto, tais indústrias utilizam o processo de lixamento de forma empírica, não otimizando-o. O objetivo deste trabalho foi comparar o comportamento das lixas de óxido de alumínio branco (OA- branco) e carbeto de silício preto (SiC- preto), analisando variáveis presentes no processo como: força, potência, emissão, vibração, desgaste, granulometria da lixa; e suas consequências no acabamento superficial da peça. Efetuou o processo de lixamento plano das amostras de Pinus elliotti, processadas paralelamente às fibras, as quais foram lixadas com lixas com grãos de OA- branco e SiC- preto em 3 condições de lixa (nova , mediamente desgastada e severamente desgastada) em 3 granulometrias ( 80, 100 e 120 mesh). Realizou-se 6 repetições para cada condição testada. A cada ensaio foi captada as variáveis de saída do processo de lixamento: força, potência, emissão e vibração. Totalizando com as duas etapas 108 ensaios. Após as amostras lixadas, verificou-se a qualidade superficial das mesmas através do levantamento da rugosidade, Ra. Por meio do experimento, pode-se concluir que lixas de OA-branco tendeu a apresentar maior força, potência, emissão e menor vibração no processo de lixamento, em relação ao SiC-preto. Porém, apresentaram acabamento superficial semelhante, para as granulometrias de 80 e 100 mesh, nas condições de lixa desgastadas. No entanto, na granulometria de 120 mesh, a rugosidade obtida através de lixa de OA-banco foi maior em relação ao SiC-preto para todas as condições da lixa devido a sua tenacidade
Keywords: Acabamentos em madeira; Usinagem; Pinus elliottii; Superficies - Preparação; Carboneto de silicio; Oxido de aluminio; Lixadeiras; Woodwork